Penggunaan Aplikasi Stockbit Sebagai Strategi Value Investing Bagi Investor Millenial - Rumbiak, Grace C.L.; Murwaniputri, Hesti; Wakarmamu, Christine (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
This service aims to provide knowledge to millennial investors in Jayapura City on how to use the stockbit application, how to identify undervalued shares using price book value (PBV), making it easier for investors to develop value investing strategies. Millennial investors are taught how to install the Stockbit application and how to read PBV charts. The results of this service found that millennial investors in Jayapura City are still minimal in using stock applications to help determine value investing strategies, millennial investors still follow advice from brokers from securities companies in Jayapura City.